2008
DOI: 10.1158/1055-9965.epi-07-2622
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Survey Mode and Asking About Future Intentions on Self-Reports of Colorectal Cancer Screening

Abstract: Colorectal cancer (CRC) screening rates are often ascertained via self-reports but can be subject to overreporting bias. Asking about intention to get screened before asking about past screening may minimize overreporting of cancer screening. In a statewide survey conducted from July through October of 2005, we embedded an experiment that tested the effect of question ordering (asking about future intention to get screened before or after asking about past screening; ''future first'' and ''future second,'' res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…For instance, asking respondents about their future intentions to get screened for cancer prior to questions about past screening has been shown reduce overreporting of screening, presumably because it gave respondents an opportunity to "save face" by demonstrating a willingness to engage in socially desirable health behaviors in the future Beebe et al, 2008).…”
Section: Comprehension/interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, asking respondents about their future intentions to get screened for cancer prior to questions about past screening has been shown reduce overreporting of screening, presumably because it gave respondents an opportunity to "save face" by demonstrating a willingness to engage in socially desirable health behaviors in the future Beebe et al, 2008).…”
Section: Comprehension/interpretationmentioning
confidence: 99%
“…For example, there is evidence that social desirability is greater when there is more contact with the interviewer, with the highest levels of social desirability emerging in face-to-face interviews, followed by telephone interviews, and then by self-administered questionnaires (Kraus and Augustin 2001). Compared to self-administered questionnaires, telephone surveys have been found to be more likely to result in underreporting for undesirable behaviors such as drug use (Johnson et al, 1989;Aquilino and LoSciuto 1990;Gfroerer and Hughes 1991;Aquilino 1992;Fendrich and Vaughn 1994) and overreporting of mammography (Armstrong et al, 2004), although other studies of cancer screening have not found an effect of mode (Beebe et al, 2008;Vernon et al, 2008). Overreporting also has been shown to be greater among participants in interventions designed to increase rates of cancer screening, possibly due to greater social desirability motivation (Jones et al, 2008).…”
Section: Comprehension/interpretationmentioning
confidence: 99%
“…Schenck et al (13) illustrate the considerable resources needed to find multiple health-care providers in various locations to provide complete data on a single study participant. One approach that was taken by several investigators (9,10,12,13) was to nest validation studies in other projects.…”
Section: Researchers and Practitioners Can Consider Opportunities To mentioning
confidence: 99%
“…Vernon et al (8) found little variation in validation rates by mode (telephone, mail, or face to face), yet the overall response rate among those contacted and eligible was modest (46%), and the study was conducted in a largely Caucasian, educated population. In a statewide survey (mail and telephone), Beebe and colleagues (10) found in a mailed survey, that asking about intention to be screened, before asking about actual recent screening behavior, statistically significantly reduced the prevalence of claims of recent screening, perhaps due to lowered pressure to give a socially desirable response. Attention to item order with adequate pretesting is needed (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation